2019
DOI: 10.1128/jvi.00728-19
|View full text |Cite
|
Sign up to set email alerts
|

Human APOBEC3G Prevents Emergence of Infectious Endogenous Retrovirus in Mice

Abstract: Endogenous retroviruses (ERV) are found throughout vertebrate genomes, and failure to silence their activation can have deleterious consequences on the host. Mutation and subsequent disruption of ERV loci is therefore an indispensable component of the cell-intrinsic defenses that maintain the integrity of the host genome. Abundant in vitro and in silico evidence have revealed that APOBEC3 cytidine-deaminases, including human APOBEC3G (hA3G), can potently restrict retrotransposition; yet, in vivo data demonstra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…Bumble mice (B6 background) were obtained from Mutant Mouse Resources & Research Centers supported by NIH (MMRRC). Tlr7 Ϫ/Ϫ mice (B6 background) and Ifnar1 Ϫ/Ϫ mice (B6 background) were from Akiko Iwasaki and Priti Kumar, Yale University (50). IL-10 Ϫ/Ϫ mice (B6 background) were from Jorge Galán and Ruslan Medzhitov, Yale University.…”
Section: Methodsmentioning
confidence: 99%
“…Bumble mice (B6 background) were obtained from Mutant Mouse Resources & Research Centers supported by NIH (MMRRC). Tlr7 Ϫ/Ϫ mice (B6 background) and Ifnar1 Ϫ/Ϫ mice (B6 background) were from Akiko Iwasaki and Priti Kumar, Yale University (50). IL-10 Ϫ/Ϫ mice (B6 background) were from Jorge Galán and Ruslan Medzhitov, Yale University.…”
Section: Methodsmentioning
confidence: 99%
“…To combat ERVs and other intragenomic parasites, mammals have developed defense systems such as Krüppel-associated box domain-containing (KRAB) zinc finger proteins (17) and PIWI-interacting RNAs (18). A3 proteins have been shown to suppress the replication of reconstructed ERVs in cell cultures (15,19) and in a transgenic mouse model (20). Furthermore, previous studies identified the signature of A3-mediated G-to-A mutations in ERVs indicating that ancient retroviruses experience attacks by A3 proteins (15,16,19,21).…”
mentioning
confidence: 99%
“…The single copy of mA3 is also under positive selection in Mus, and the positively selected residues in the catalytically active A3Z2 domain line the substrate groove that accommodates nucleic acids [ 160 ]. The demonstration that A3 proteins can also more broadly restrict replication of endogenous retroviruses and retrotransposons, indicate that A3 mutators have been in conflict with retroelements throughout mammalian evolution [ 175 , 176 , 177 , 178 , 179 ]. Furthermore, A3G has been demonstrated to have broader antiviral activity that can block HBV, replication of which includes a reverse transcription step [ 180 , 181 , 182 ].…”
Section: Retroviral Restriction Factorsmentioning
confidence: 99%